TRANSFORMATION OF BEHAVIORAL ARCHITECTURE: SPATIAL AND PSYCHOLOGICAL STRATEGIES IN DESIGNING A SOCIAL CENTER FOR STREET CHILDREN IN MEDAN CITY - Putri Wadda Nabila; Hajar Suwantoro (CV. Denasya Smart Publisher, 2026)
The urban development of Medan, Indonesia, reflects a growing social challenge related to the presence of street children living in vulnerable conditions. Official data from the Social Service of North Sumatra indicate that there are approximately 525 street children. Current social facilities often adopt a warehousing model, referring to large scale, institutionalized mass shelter systems that tend to neglect the psychological needs of users. This is particularly concerning given that 92% of street children suffer from profound trauma. This study proposes a Trauma-Informed Healing Architecture (TIHA) framework for a Social Center in Medan Selayang. By synthesizing Irwin Altman’s Territoriality and J. Douglas Porteous’s